'Ti Aumâs Oms': notes on a configuration of the NE 51/ series houses in Windhoek, Namibia. - Boulton, Jack (Critical African Studies, 2026)
This article examines the NE 51/ series 'matchbox' houses in Dolam, a suburb of the township Katutura, in Windhoek, Namibia – structures originally built during the late 1950s and early 1960s as a part of the Apartheid government's social engineering project to instil the values of 'Western style' Modernist living. Through a case study of three houses, the article explores how residents have redefined these colonial-era spaces. The study reveals that these homes, often owned and headed by women, have undergone significant renovations to accommodate multi-generational living. Moreover, the relationships between neighbouring households form a 'configuration' that transcends the physical boundaries of individual houses. The presence of a shared gate and the continuous exchange of resources and support illustrate how kinship networks extend beyond singular dwellings. Drawing on extensive ethnographic fieldwork, this article contributes to broader discussions on the intersection of housing, kinship, and urban life in post-Apartheid Namibia. It challenges conventional understandings of township houses as isolated units, instead positioning them as interconnected spaces where social ties are actively maintained and reconfigured.